Impact Of Technological Innovations For Coffee Production In Adverse Weather Conditions - Flavia Maria de Mello Bliska; Patricia Helena Nogueira Turco; Celso Luis Rodrigues Vegro; Thomaz Fronzaglia; Sérgio Tosto (European Regional Science Association (ERSA), 2013)
A major concern of the Brazilian coffee growers is closely related to the quantitative and qualitative impacts on the coffee sector as a result of possible climate changes, particularly regarding the production of Arabica coffee varieties, which have better beverage quality. This is because low temperatures (below 18 ° C) or elevated (above 23 ° C), causes the blocking of the biological functions responsible for the development of coffee tree, resulting in abortion of flowers and consequently in reducing crop yields and grain quality. Moreover, water deficits or poor water distribution (below 1200mm or above 1800mm annually) can also cause damage during flowering and fruiting, and consequent drop in production and final product quality. Among the available solutions to minimize the negative effects of climate change, stand irrigation, forestation and new varieties of coffee. Irrigation and trees can be used to circumvent both excess heat and cold as well as to protect the crops from frost. Among the technologies developed at the Agronomic Institute - IAC throughout its 126 years of research on coffee, just stand out studies on irrigation and forestation and development of varieties like Obat\~a, which has shown good prospects for production in hot regions, traditionally considered marginal for the production of Arabica coffee, since accompanied by irrigation. However, the effects that have been observed with the use of production systems irrigated and shaded, and the cultivation Obat\~a not yet been quantified. As a result, this study aims to quantify the environmental, economic and social changes that have resulted from use of those technologies in certain regions of Brazil. To scale the impacts of those technologies we have developed a system consisting of a set of indicators aimed at evaluation of the contribution of technological innovation to environmental, social and economic development of an agricultural activity. The system involves: 1) Collection of data on general technology; 2) Application of questionnaires with selected adopters and entering data on indicators of impact spreadsheets via MS-ExcelÒ platform for obtaining quantitative results and impacts indexes of technology selected; and 3) Analysis and interpretation of indices, which range between -15 and +15. The measurement of these impacts is relevant to the grower, because, as it can know the regional performance of available technologies and make decisions about their possible use, and also for the institutions of Research and Development, which can evaluate and update guidelines of their respective work programs.
Keywords: Q15; 330; Climate change; Impacts of technologies; Sustainable development; Regional development